2023
DOI: 10.1097/aog.0000000000005287
|View full text |Cite
|
Sign up to set email alerts
|

Vasa Previa

Yinka Oyelese,
Ali Javinani,
Alireza A. Shamshirsaz

Abstract: Vasa previa refers to unprotected fetal vessels running through the membranes over the cervix. Until recently, this condition was associated with an exceedingly high perinatal mortality rate attributable to fetal exsanguination when the membranes ruptured. However, ultrasonography has made it possible to diagnose the condition prenatally, allowing cesarean delivery before labor or rupture of the membranes. Several recent studies have indicated excellent outcomes with prenatally diagnosed vasa previa. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
37
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 106 publications
0
37
0
Order By: Relevance
“…Delivery by Cesarean section prior to rupture of the membranes largely prevents perinatal death [4][5][6] . Several studies have documented the feasibility of screening routinely for vasa previa and the impact of screening in preventing death 4,7,8 . Consensus guidelines recommend sonographic examination of the placental cord insertion when feasible 4 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Delivery by Cesarean section prior to rupture of the membranes largely prevents perinatal death [4][5][6] . Several studies have documented the feasibility of screening routinely for vasa previa and the impact of screening in preventing death 4,7,8 . Consensus guidelines recommend sonographic examination of the placental cord insertion when feasible 4 .…”
mentioning
confidence: 99%
“…Several studies have documented the feasibility of screening routinely for vasa previa and the impact of screening in preventing death 4,7,8 . Consensus guidelines recommend sonographic examination of the placental cord insertion when feasible 4 . While most early reports indicated that vasa previa results from velamentous cord insertion, Catanzarite and colleagues first described in 2001 Type-2 vasa previa, in which the cord insertion was normal but unprotected fetal vessels ran through the membranes between the main placental mass and an accessory lobe 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
V asa previa refers to exposed unprotected fetal vessels that run through the membranes over the cervix. 1,2 This condition is associated with a high risk for perinatal death when not detected prenatally. [3][4][5] However, vasa previa is a condition that demonstrates the remarkable impact of ultrasound in dramatically improving perinatal outcomes.
…”
mentioning
confidence: 99%
“…However, no such safety has ever been demonstrated for vaginal delivery with vasa previa. 2 Yet, some publications continue to define vasa previa as fetal vessels that lie within 2 cm of the internal os. In the absence of any data to support this distance as being safe, one wonders why so many adopt this distance definition.…”
mentioning
confidence: 99%